Determinants of adoption of accelerated rice breeding - CGIAR Research Program on Rice (2021)
We develop a proof of concept for the monitoring and assessment of technological and institutional change in breeding programs which will play a crucial role in the CGIAR Genetic Innovation Initiatives.